Analysis of occupational accidents during the chainsaws use in Andalucía - López-Toro, Alberto Antonio; Pardo-Ferreira, María del Carmen; Martínez-Rojas, María; Carrillo Castrillo, Jesús Antonio; Rubio-Romero, Juan Carlos (Elsevier, 2021)
The chainsaw is one of the most dangerous pieces of work equipment in the field of occupational health and safety. Analysis of occupational accidents involving chainsaws is scant. The aim of this study is to provide a faithful description of registered occupational accidents related to the chainsaw in the Andalusian region of Spain. In total, 373 accidents were studied, and in which characteristics of the injured person, enterprise, workplace and sequence of the event were studied. It was determined that the injured victim tended to be a male worker between 30 and 59 years old from the forestry or agricultural sector. Typically, the accident took place in the month of February or March. As for the characteristics of the accident, normally it occurred in forestry or agricultural areas during associated tasks, with the loss of control of the chainsaw, leading to contact with the blades, causing open wounds to the leg, knee or fingers. A specific feature in Andalusia is the influence of the use of the chainsaw in olive tree pruning and in the task of preventing forest fires. It is important to develop an international training standard and apply it to any worker who uses the chainsaw. The manufacturers of chainsaws should be involved in the prevention of accidents at work while using their devices, in terms of safe use to prevent the loss of control of the chainsaw, and in promoting the mandatory use of personal protective equipment to reduce or eliminate injuries caused by cuts, especially to the upper extremities.
https://openpolicyfinder.jisc.ac.uk/id/publication/16957
Keywords: Accidentes de trabajo - Andalucía; Motosierras - Accidentes; Seguridad industrial; Chainsaw; Occupational accidents; Safety; Injured workers; Forestry; Agriculture